THE IMPACTS OF MODELED-READING STRATEGY ON STUDENTS’ REASONING SKILL ABILITY - Nyak Mutia Ismail; Ida Muliawati; Rusma Setiyana (JURNAL ILMIAH DIDAKTIKA: Media Ilmiah Pendidikan dan Pengajaran, 2022)
In spite of being included into receptive skill, reading is no longer considered as a passive activity of learning. It is known that readers should be actively engaged during the reading process in attempt to achieve comprehension. This study sought the impacts of the application of modeled reading in increasing students’ reasoning skill, both verbally and logically. Conducted by following quasi experimental characteristics, this study employed one-group pretest post-test design. There were 23 college students involved as the samples who were given a pretest, teaching treatment, and a post-test. The instruments used were two types of test: verbal reasoning test and logical reasoning test. Each set consists of 10 questions. During the data collection or test, the students were given 25 minutes to answer each set, for both the pretest and the posttest. Later, the data were analyzed using normality test and t-test to see if there is any significance increase after the treatment. The results unveil that both skills enhance after the treatment with modeled reading. First, students’ ability in verbal reasoning ability increases from 34.7 to 77 and logical reasoning ability increases from 65 to 83.4 in average. In conclusion, applying modeled reading can expand students’ cognitive ability in sharpening their verbal and logical reasoning which are beneficial during their learning, especially in reading comprehension.